Analisis Penerapan Manajemen Strategi Pada Klinik Pratama An-Nisa Medika - Safitri, Dian Riski; Trianto, Eko; Nareshvahri, Janatika Fitri; Rahmadani, Sesilia (Jurnal Manajemen Strategis: Jurnal Mantra, 2025)
This study examines the application of strategic management at Anisa Medika Main Clinic. The study aims to examine the strategic management process, identify internal and external elements, and measure strategic effectiveness with the goal of improving the quality of health services. The researcher uses a qualitative descriptive methodology that includes in-depth interviews with five selected informants (managers, administrative staff, pharmacists, operational staff, and medical personnel), participatory observation, and analysis of internal documents. The data analysis method used is the Miles & Huberman method, employing source-based triangulation and methods to ensure credibility. The results of this study indicate that the institution implements a comprehensive strategy based on an Islamic perspective, leading to full accreditation. However, digital shortcomings require WO (infrastructure improvement) and ST (group differentiation) approaches. The WO strategy is recommended for promotional expansion, while the ST strategy is suggested for system innovation. These results enrich the bibliography on health management and indicate that the integration of Ihsan values strengthens patient engagement despite competition.